Critical narrative review of the applications of near-infrared spectroscopy technology in sports science - Sendra-Pérez, C.; Encarnación-Martínez, A.; Priego-Quesada, J. I. (Sensors, 2025)
Near-Infrared Spectroscopy (NIRS) is a noninvasive technology used to monitor muscle oxygenation in sports science. Since its introduction in 1977, NIRS has evolved into a valuable tool for assessing physiological responses during exercise and rehabilitation. The history of NIRS dates back to early hemoglobin studies in the 19th century, with significant advancements in pulse oximetry during World War II. By the late 1980s, NIRS had become widely used in sports science, allowing researchers to evaluate muscle perfusion and metabolic thresholds in various activities. NIRS applications in sports include determining exercise thresholds, monitoring muscle oxygenation during training, assessing asymmetries between limbs, and evaluating mitochondrial capacity. Studies have explored its use in both team and endurance sports, highlighting its role in optimizing performance and preventing injuries. Beyond sports, NIRS technology is expanding into clinical fields, aiding in rehabilitation and patient monitoring. This critical review has identified several key areas for future research, including the need to clarify methodological influences, strategies to minimize the impact of adipose tissue on NIRS measurements, the importance of conducting longitudinal studies, increased research on sex-specific effects, and a greater emphasis on field-based studies. With continued advancements, NIRS is expected to further enhance our understanding of muscle physiology and human performance, making it a crucial tool in athletic performance assessment and clinical practice.